QCD sum rule study on the fully strange tetraquark states of JPC = 2++ - Dong, Rui-Rui; Su, Niu; Chen, Hua-Xing; Cui, Er-Liang (Frontiers in Physics, 2023)
We apply the QCD sum rule method to systematically study the fully strange tetraquark states with the quantum number JPC = 2++. We construct both the diquark–antidiquark and mesonic–mesonic currents and calculate both their diagonal and off-diagonal correlation functions. Based on the obtained results, we further construct three mixing currents that are nearly non-correlated. We use one mixing current to extract the mass of the lowest-lying state to be 2.03−0.15+0.16 GeV, which can be used to explain f2(2010) as a fully strange tetraquark state of JPC = 2++. This state was observed by BESIII in the ϕϕ channel, and we propose to confirm it in the η(′)η(′) channel.